2022
DOI: 10.3389/fpsyg.2021.792989
|View full text |Cite
|
Sign up to set email alerts
|

Maternal History of Adverse Experiences and Posttraumatic Stress Disorder Symptoms Impact Toddlers’ Early Socioemotional Wellbeing: The Benefits of Infant Mental Health-Home Visiting

Abstract: BackgroundThe present study examined the efficacy of the Michigan Model of Infant Mental Health-Home Visiting (IMH-HV) infant mental health treatment to promote the socioemotional wellbeing of infants and young children. Science illuminates the role of parental “co-regulation” of infant emotion as a pathway to young children’s capacity for self-regulation. The synchrony of parent–infant interaction begins to shape the infant’s own nascent regulatory capacities. Parents with a history of childhood adversity, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 108 publications
(132 reference statements)
0
10
0
Order By: Relevance
“…It may be that mothers with a history of out‐of‐home care who also experience poorer mental health and lower educational attainment face additional barriers to enrollment and engagement in home visiting. While previous research suggests that the children of mothers who have experienced maltreatment or trauma have high rates of developmental delay (Folger et al., 2018), there are several other contextual factors (e.g., parenting practices, access to early care, and education) that could contribute to why no significant differences in screening results between groups were detected in this study, as other home visiting research has shown improvement in the mental health of infants and children of mothers with a history of maltreatment (Ribaudo et al., 2022).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…It may be that mothers with a history of out‐of‐home care who also experience poorer mental health and lower educational attainment face additional barriers to enrollment and engagement in home visiting. While previous research suggests that the children of mothers who have experienced maltreatment or trauma have high rates of developmental delay (Folger et al., 2018), there are several other contextual factors (e.g., parenting practices, access to early care, and education) that could contribute to why no significant differences in screening results between groups were detected in this study, as other home visiting research has shown improvement in the mental health of infants and children of mothers with a history of maltreatment (Ribaudo et al., 2022).…”
Section: Discussionmentioning
confidence: 68%
“…Those with a history of out-of-home care experience poorer mental health outcomes compared to the general population and, among those who become parents, face increased barriers to supporting the mental health and wellbeing of their infants (Larrieu et al, 2008;Shpiegel et al, 2017Shpiegel et al, , 2020. Early childhood home visiting programs for new mothers and their children could address some of these challenges (Ribaudo et al, 2022;Sama-Miller et al, 2019). The purpose of this study was to examine differences in engagement in home visiting for mothers with and without a history of out-of-home care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the higher prevalence of PTSD in parents of preterm newborns (up to 53% in mothers and 33% in fathers) ( 4 ) with respect to general postpartum population (20.7% in mothers, 7.2% in fathers at 1 month post-partum) ( 58 ), interventions for PTSD prevention could be offered to all parents of NICU-admitted infants. A further reason for offering interventions for PTSD prevention and treatment to all parents of preterm babies is that parents with PTSD have greater difficulties in co-regulating their infants, thus increasing the risk of their children exhibiting social and emotional problems such as anxiety, aggression, depression and disorganized behavior ( 59 , 60 ). Given other long-term consequences of parental PTSD on infants [e.g., poorer cognitive outcome ( 61 ), sleeping and eating difficulties ( 62 )], and the importance of the first months of life for brain and stress-system development, prevention and early treatment of parental PTSD is even more important ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the coping trajectory group, parents focus on actively coping with or fighting against the distressing psychological problems. However, this parental struggle itself may serve as a traumatic stimulus for children (Ribaudo et al, 2022). When children witness their parents struggling with trauma events, they may perceive the magnitude of their parents' traumatic experience, which could potentially result in higher levels of PTSD symptoms in children.…”
Section: Discussionmentioning
confidence: 99%